TRANSFORMASI TATA KELOLA EKONOMI PUBLIK MENUJU GOOD GOVERNANCE - Andi Zulkarnain; Khanan Yusuf; Nian Riawati; Diah Hari Suryaningrum; Aryo Prakoso (POLITEKNIK LP3I JAKARTA, 2026)
Transforming public economic governance through digitalization is a crucial agenda for realizing the principles of good governance in a globalized world. However, field dynamics indicate a gap between technological infrastructure readiness and stakeholder engagement behavior. This qualitative research aims to deeply explore the processes, structural-cultural barriers, and dimensions of human behavior in the implementation of digital platforms in the public economic sector. Using a descriptive-analytical case study design, data were collected through in-depth interviews with purposively selected key informants, field observations, and official documents. Data validity was tested using source and method triangulation techniques, which were then analyzed qualitatively through a thematic analysis approach. The results show that structurally, digitalization has successfully overhauled traditional bureaucracy, cut corrupt service chains, and increased transparency and accountability in public finances. However, this success faces cultural challenges in the form of resistance to change, a silo mentality, and low user behavioral intentions due to limited digital literacy and system perceptions (effort expectancy). Based on the Unified Theory of Acceptance and Use of Technology (UTAUT), weak facilitating conditions are the primary factor inhibiting optimal system adoption. This study concludes that good governance cannot be achieved solely through normative regulations and hardware procurement, but rather requires simultaneous integration with strengthening digital literacy capacity and user behavioral interventions. The policy implications of this research emphasize the importance of simplifying digital procedures and extensive training to create an efficient and accountable public economic system